Natural AMPK Activators in Cardiovascular Disease Prevention - Heidary Moghaddam, Reza; Samimi, Zeinab; Asgary, Sedigheh; Mohammadi, Pantea; Hozeifi, Soroush; Hoseinzadeh‐Chahkandak, Fatemeh; Xu, Suowen; Farzaei, Mohammad Hosein (Frontiers in Pharmacology, 2022)
Cardiovascular disease (CVD), as a life-threatening global disease, is receiving worldwide attention. Seeking novel therapeutic strategies and agents is of utmost importance to curb CVD. AMP-activated protein kinase (AMPK) activators derived from natural products are promising agents for cardiovascular drug development owning to regulatory effects on physiological processes and diverse cardiometabolic disorders. In the past decade, different therapeutic agents from natural products and herbal medicines have been explored as good templates of AMPK activators. Hereby, we overviewed the role of AMPK signaling in the cardiovascular system, as well as evidence implicating AMPK activators as potential therapeutic tools. In the present review, efforts have been made to compile and update relevant information from both preclinical and clinical studies, which investigated the role of natural products as AMPK activators in cardiovascular therapeutics.